Changing higher education in East Asia - Xu, Xin; Marginson, Simon (London [England] : Bloomsbury Academic, 2022)
"Higher education in East Asia is developing rapidly and attracting global attention. However, the region faces tensions during the internationalisation process. What is the regional character of East Asian higher education? What do these countries have in common and how are they different? How do internationalisation, indigenisation, westernisation, and globalisation interplay in this region? Bringing together experts from Australia, China, Hong Kong, Japan, South Korea, Taiwan, the UK and Vietnam, this book delves into these dynamics, offering original perspectives and robust evidence. It covers key issues around internationalisation and globalisation, such as the role of higher education in furthering the global public and common good, world-class universities, world citizenship education, the internationalisation of the humanities and social sciences, the governance of science, student and academic mobility, and the challenging question of how to advance regional cooperation"
The ensemble of diverse music : internationalisation strategy and endogenous agendas / Simon Marginson and Xin Xu -- Global public good in Korea as jeong / Olga Mun and Yunkyung Min -- Tianxia weigong as a Chinese approach to global public good / Lili Yang -- Global and world citizenship in Chinese education / Arzhia Habibi -- World-class universities and global common good / Lin Tian and Nian Cai Liu -- Regional higher education cooperation in Japan / Christopher D. Hammond -- Internationalisation of Chinese humanities and social sciences / Xin Xu -- Internationalisation of higher education in Taiwan / Julie Chia-Yi Lin -- Geopolitics and internationalisation of higher education in Vietnam / Ly Thi Tran, Huong Le Thanh Phan, Huyen Bui -- Agency of international student-migrants in Japan / Thomas Brotherhood -- Motivations and work roles of international faculty in China / Futao Huang -- The Covid-19 pandemic and international higher education in East Asia / Ka Ho Mok.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Education, Higher -- East Asia; Educational change -- East Asia; Education and globalization -- East Asia; Educational strategies & policy,Higher & further education, tertiary education; Electronic books